2018
DOI: 10.1002/ccd.27854
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, single‐center, randomized study to assess whether automated coregistration of optical coherence tomography with angiography can reduce geographic miss

Abstract: Objective We sought to evaluate whether automated coregistration of optical coherence tomography (OCT) with angiography reduces geographic miss (GM) during coronary stenting. Background Previous intravascular ultrasound or OCT studies have showed that residual disease at the stent edge or stent edge dissection was associated with stent thrombosis or edge restenosis. This has been termed GM. Methods Two hundred de novo coronary lesions were randomized in a 1:1 ratio to OCT‐guided percutaneous coronary intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Therefore, ACR may optimize stent sizing -including coverage of vulnerable plaques within the edges of the coronary lesions and optimal stent-positioning outside a vulnerable plaque to avoid incident edge dissections [16]. In a recent trial comparing ACR-with OCT-guided PCI, although no differences were observed in terms of LGM (27.6% with ACR vs. 34.0% with OCT; p = 0.33), a 50%-reduction in the risk of distal stent edge dissection after ACR-guided PCI was observed similar to this study [17]. Differences between the studies may at least in part be due different patient populations included and differences in the study protocols.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, ACR may optimize stent sizing -including coverage of vulnerable plaques within the edges of the coronary lesions and optimal stent-positioning outside a vulnerable plaque to avoid incident edge dissections [16]. In a recent trial comparing ACR-with OCT-guided PCI, although no differences were observed in terms of LGM (27.6% with ACR vs. 34.0% with OCT; p = 0.33), a 50%-reduction in the risk of distal stent edge dissection after ACR-guided PCI was observed similar to this study [17]. Differences between the studies may at least in part be due different patient populations included and differences in the study protocols.…”
Section: Discussionsupporting
confidence: 83%
“…Differences between the studies may at least in part be due different patient populations included and differences in the study protocols. In the present study, the primary endpoint was recorded immediately after achieving an angiographic optimal PCI result as compared to endpoint assessment after additional PCI-optimization by OCT or ACR, respectively, which may result in more frequent optimization procedures including additional stenting in case of inacceptable lesion coverage for OCT-guided PCI and consequently equalize potential differences between groups achieved by ACR [17].…”
Section: Discussionmentioning
confidence: 99%
“…The software presents the selected distal and proximal landing sites as markers on the co-registered angiography to guide precise stent implantation (Supplementary Figure 4), eliminating the perils of landing the stent edges in the angiographically normal appearing reference segments where plaque burden may be extensive 23 . In a randomised study, OCT-angiography co-registration aided in more precise stent deployment, eliminating large geographic miss (>5 mm), and resulted in a trend towards reducing major stent edge dissection compared to angiography guidance 24 . Similar findings were reported in observational studies reporting geographic miss with a length of ≈5 mm with angiography guidance, stent coverage guided by angiography alone missing OCTidentified lesions in 70% of patients 25 , and changes in the device landing zone and stent length prompted by OCT co-registration in ≈20% of patients 26,27 .…”
Section: Angiographic Co-registrationmentioning
confidence: 99%
“…In addition, OCT-angiography coregistration OCT-angiography coregistration leads to accurate stent implantation with respect to longitudinal geographic location in coronary arteries. A previous study demonstrated that the distance discrepancy between the planned stent location and the actual implanted stent location was significantly shorter in the coregistration group than in the no coregistration group (1.9 ± 1.6 mm vs. 2.6 ± 2.7 mm, P = 0.03) [8]. In addition, the long-distance discrepancy of ≥ 5 mm tended to be less frequent in the coregistration group than in the no coregistration group (4% vs. 12%, P = 0.07) [8].…”
Section: Discussionmentioning
confidence: 85%